Odpowiedź:
[tex]a)\ \ 9x+18x-11x=(9+18-11)x=(27-11)x=16x\\\\b)\ \ -7+8y+10-2y-3=-10+10+8y-2y=0+6y=6y\\\\c)\ \ 4x-8-10x-9=(4-10)x-8-9=-6x-17\\\\d)\ \ -5x+4y-7x+3y=(-5-7)x+(4+3)y=-12x+7y[/tex]
[tex]e)\ \ 11a-9a+b+4b-a-12b+1=11a-9a-a+b+4b-12b+1=a-7b+1\\\\f)\ \ 2,6y+3y-x-1,5x-1,2y=5,6y-1,2y-2,5x=4,4y-2,5x\\\\g)\ \ -2\cdot7y=-(2\cdot7)y=-14y\\\\h)\ \ \frac{2}{3}x\cdot0,75=\frac{2}{3}x\cdot\frac{75}{100}=\frac{\not2^1}{\not3_{1}}x\cdot\frac{\not3^1}{\not4_{2}}=x\cdot\frac{1}{2}=\frac{1}{2}x\\\\i)\ \ 32x:(-4)=-32x:4=-8x\\\\j)\ \ \frac{1}{3}x+4y+\frac{2}{3}-5y=\frac{1}{3}x-y+\frac{2}{3}[/tex]